The role of the school principal: challenges and possibilities of your professional acting, while facilitator of the teaching-learning process (Research, Society and Development, 2020)
This study aims to understand how the school principal can be a facilitator of the teaching-learning process and to identify the challenges encountered and the possibilities in in that process. This is a field research, with a qualitative approach, carried out in a public school in the municipality of Cariré-Ceará, in August 2018. Data collection occurred through participant observation and a questionnaire. In view of the interpretation of the findings, it was understood that the director is not only capable of performing administrative aspects, but can also work together with teachers to assist in the development of the teaching-learning process; that it is with willpower, in dialogue and in the face of pedagogical practices, that he can build methodologies that help students in the teaching and learning process, since the school administration team influences and facilitates this process that defines the social mission , politics and technique of the school today. Among the challenges of the teaching-learning process, the director interviewed in this study highlighted school dropout and, as a leader and facilitator, uses the field of motivation as a strategy to overcome this fact. Thus, school managers, as well as other education professionals, need to be in a constant formation process, taking into account that they are professionals who form other people.